PENGARUH PARAMETER OPERASI PADA PROSES TRANSESTERIFIKASI MINYAK JELANTAH MENGGUNAKAN KATALIS TULANG SAPI TERHADAP YIELD DAN DENSITAS BIODIESEL - Sidabutar, Elizabeth Desfelia Ciciolini; Sujana, I Made Ivan Wijayarta Cakra; Oktavia, Fika Dwi; Putri, Nita Ariestiana; Sari, Martina Puspita (Tanjungpura University, 2025)
This study uses a heterogeneous catalyst derived from bovine bones to examine the effect of calcination temperature, calcination time, and mass catalyst loading on the yield and density of biodiesel synthesized from waste cooking oil. The bones were cleaned, pressure-cooked, dried, ground, sieved, and then calcined at temperatures of 800 °C and 1000 °C for 2, 4, and 6 hours. The transesterification process was conducted at 65 °C for 1 hour with 4% and 6% catalyst loadings by weight of the waste cooking oil. The results showed that a calcination temperature of 1000 °C produced more stable and active catalysts, thus increasing biodiesel yield, especially at longer calcination times. The highest yield of 72.81% was achieved using 6% catalyst calcined at 1000 °C for 6 hours. In contrast, at 800 °C, the yield tended to decrease or remain inconsistent as calcination time increased. The biodiesel density ranged from 0.944 to 0.955 g/mL, slightly higher than the standard value, possibly due to incomplete conversion or residual glycerides. These findings indicate that calcination temperature, calcination time, and catalyst loading play a significant role in the efficiency of biodiesel synthesis using bovine bone catalysts.